History of Kannur and North Malabar : Kolatiri, Arakkal and Mysore Sultans - More, Leena, (Brill | Manohar Publishers & Distributors, 2024)
The present work explores the historical origins and early development of Cananore and North Kerala region, till they were annexed by the British in 1792, when the said place became part of Madras Presidency under the British administration. It traces back its journey from the ancient Sangam age, independent Kingdom of Nannan to the rule of the Mushika dynasty during the medieval period, and it ends with the emergence of the Kolatiri dynasty that succeeded the Mushikas. This book places a particular emphasis on the Arakkal family, a branch that originated from the Kolatiris. The Arakkals controlled the large tracts of land including the Laccadive Islands. As Dutch expended its influence in Malabar, at the expense of the Portuguese, the Arakkals successfully asserted their independence in Malabar. The arrival of the Mysore Sultans helped the Arakkals to shake off the domination of the Kolatiris. However, the defeat of Tipu Sultan at the hands of the English East India Company in 1792, sealed the fate of the Arakkals, as well as the Kolatiris. The author has put to good use her knowledge of Malayalam, French, and English sources to reconstitute the history of Kannur and north Malabar until 1792.